Toward user mobility for OFDM-based visible light communications - Hong, Yang; Chen, Lian-Kuan (Optics letters, 2016)
We propose and experimentally demonstrate a mobile visible light communications (mobi-VLC) transmission system. The impact of user mobility on the performance of the mobi-VLC system is characterized, and we propose the use of the channel-independent orthogonal circulant matrix transform (OCT) precoding to combat the packet loss performance degradation induced by mobility. A mobile user terminal is used to detect the signal from a blue laser placed at 1 m away from the moving track. Various moving speeds (20, 40, 60, and 80  cm/s) and lateral moving distances (30, 40, and 50 cm) of the user terminal are investigated. The effectiveness of the OCT precoding is evaluated by the comparison with the conventional orthogonal frequency division multiplexing (OFDM) scheme and the adaptive-loaded discrete multi-tone (DMT) scheme. Experimental results show that the system performance degrades with the increase in user mobility speed and in moving distance. Furthermore, the OCT precoding provides performance improvement that is superior over that of conventional OFDM schemes, and it exhibits lower packet loss rate than that of adaptive-loaded DMT. No packet loss for 300  Mb/s transmission is achieved with a 30 cm lateral moving distance at 20  cm/s.